Mind And Concepts Related To Mind In Tabsira Al- Adilla - GÖKALP, Yusuf; ADYLCAN KYZY, Tolgonai (Scientific Journal of Faculty of Theology, 2020)
Abu’l-Muin an-Nasafi is one of the important representatives of the, religious understanding of "Matrudism" after Abu Mansur al-Matrudi. He, through clarification of the Kalamic views of matrudism, as well as providing answers to criticism of Matrudism, made an important contribution to the development and transformation of the madhhab Matrudiyya into a Kalamic School. Abu’l-Muin an-Nasafi has such important works as Tabsiratu’l-Adilla, At-Tamhid, Bahru’l-Kalam, Sherkh Tavilatu’l-Kur’an. This study examined the term reason and terms related to reason present in the work of Abu’l-Muin an-Nasafi, Tabsıratu’l-Adilla, which is his most important work in the field of Kalam. Abu’l-Muin an-Nasafi as well as Abu Mansur al-Matrudi in his works gives a special place to reason and reason of reason. This article deals with such topics as the vocabulary meaning of the word reason, mentioned in the Tabsıratu’l-Adilla, rational evidence in Kalam, and is also considered as used in the work terms related to the mind, such as ma’rifat, idrak, tafakkur, fakhm, zaka, taamul, rei, basirat, lyub and zikhn.